Company profile video design As a starting business introduction media - parwono, Toto; Chandra Dewi, Sushanty; Subagiyo (ASIAN PUBLISHER, 2022)
It would be nice if each company had certain media as open-source information for society and one of them is a company profile. It is regularly used by a company to deliver and spread information for any occasion such as awareness, image/reputation, and promotion. Along with the changing trend within the digital era, recent society is preferred to consume information in audio-visual format. Therefore, the existing company profile should be adjusted to the recent trend and made more interesting. According to the background, this study aimed to create a company profile for a growing start-up business in video format. This study used Research and Development (R & D) method as a way to examine and solve the issue. The process itself contains defining, designing, developing, and disseminating. Those steps then resulted in a company profile video that showed the positive image of the company and could be used for any occasion. Besides, the video created also increases the information asset of the company.